Kajian Teknis Pemanfaatan Bio-Massa Di Pabrik Pengolah Minyak Sawit Berkapasitas 30 Ton Perjam Dengan Sistem Kongenerasi - Hermanto, Bangbang (Faculty of Engineering, Universitas Tanjungpura, 2013)
Abstract This thesis examines the potential of bio-mass waste generated from palm oil mills with a capacity of 30 tonnes which will be converted into heat energy for process and electrical energy to drive the motors, in which the two energy sources is a major requirement in the processing of palm oil. Number of factories operating in West Kalimantan is 28 mills with a total capacity of processing fresh fruit bunches by 1,190 tons / hour. Potential sources of renewable energy from waste bio-mass produced: 21.5% empty fruit bunches, fiber 12.5%, and 5.1% shell. From the calculation and field studies, the potential of solid waste are: fibers and fibers using super heat boiler obtained at 44.02% thermal efficiency, power output of 2,064 MW, and the power can be used for external plant of 1,464 mW.Steam for the process, is obtained from the steam turbine output, which should be above one atm pressure then used non-condensing turbine one level, with the required generator capacity of 2.58 kVA. Keywords cogeneration, super heat, thermal efficiency, type of turbine and generator capacity, fiber, shell.